Identifying the Determinants of Poverty in Rural and Urban India - G.K. Jha , N. Sivaramane , R. N. Padaria, N.P. Singh, Ranjit Kumar (Indian Journal of Extension Education, 2022)
A recent study on poverty highlights serious conceptual anomalies in the measurement of poverty and in selection of variables which can throw more light on contentious issues of deciphering the determinants of poverty. Identification of such variables still remains a challenging task for the researchers and policy makers. in this paper, an attempt is made to identify the factors influencing determination of poverty in rural and urban settings using logit model. Further marginal effects and elasticities were estimated which provided better interpretation of economic variables. The findings explicitly provide insights about the direction and magnitude of the impact of variables on the incidence of poverty. It was found that the proportion of children in the household appeared to be the foremost factor in augmenting poverty; however this may be due to the causative effect on poverty itself. Moreover, infrastructure and occupational variables were found to be more. Influencing factors in decreasing poverty in rural and urban India, respectively. The study’ confers that the household specific variables were having pronounced influence on poverty as compared to state specific variables. The study advocated the need to implement the family planning programmes, targeting literacy campaigns in an effective way and enhancing minimum wages coupled with better infrastructure for improved livelihood and reduced poverty.